1992
DOI: 10.1055/s-2006-961411
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Analgesic Effects of an Aqueous Extract ofHarpagophytum procumbens

Abstract: The dried aqueous extract of Harpagophytum procumbens (Pedaliaceae) and its main iridoid glycoside, harpagoside, have been evaluated for anti-inflammatory and analgesic effects in mice and rats, in order to validate or invalidate the involvement of this compound in such properties. This extract exerted significant and dose-dependent anti-inflammatory and analgesic effects, from the dose 100 mg of dried secondary roots/kg, the first being obtained on an acute inflammatory process (carrageenan-induced edema test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(95 citation statements)
references
References 1 publication
4
83
0
5
Order By: Relevance
“…Nevertheless, carrageenan-induced paw edema was not affected by the isolated harpagoside constituent. This signifies that harpagoside may not have an anti-inflammatory effect, at least in the dosage used in this study [55,56]. This suggests that other HP constituents may be responsible for the antiinflammatory effect.…”
Section: Harpagophytum Procumbens Fam Pedaliaceaementioning
confidence: 75%
See 1 more Smart Citation
“…Nevertheless, carrageenan-induced paw edema was not affected by the isolated harpagoside constituent. This signifies that harpagoside may not have an anti-inflammatory effect, at least in the dosage used in this study [55,56]. This suggests that other HP constituents may be responsible for the antiinflammatory effect.…”
Section: Harpagophytum Procumbens Fam Pedaliaceaementioning
confidence: 75%
“…Although, it is worthy to mention that the whole-plant extracts seem to have a better therapeutic effect than those obtained from isolated parts [60]. Harpagoside inhibited in vitro the synthesis of various proinflammatory mediators via suppression of iNOS and COX-2 expression through inhibition of NF-kappa B activation [61], but showed no anti-inflammatory activity in one animal model of inflammation (carrageenan-induced paw edema) [55]. The scientists suggested that other phytochemicals than harpagoside may be contributors to the anti-inflammatory effect of HP [55,62].…”
Section: Harpagophytum Procumbens Fam Pedaliaceaementioning
confidence: 99%
“…Plant sterols display their anti-inflammatory activity through inhibition of the secretion of interleukin-6 and tumor necrosis factor-α (Bouic, 2001). Phytosterols EVALUATIoN oF THE ANTI-INFLAMMAToRy AND ANTI-ARTHRITIC EFFECTS oF SoME PLANT ExTRACTS Also, the reduction in body weight gain may be due to muscle wasting in experimental arthritis, which seems to be due to enhanced protein breakdown by the ubiquitin-proteasome proteolytic pathway (Lecker et al, 2004;Granado et al, 2005). It was noticed that food intake was also reduced significantly, which may share in the reduction of body weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…현지에서는 외상, 월경장애, 출산통, 소화장애, 관절염 등 에 사용하였으며 2) , 1960년대 천수근의 Secondary roots 으로부터 얻어진 추출물이 효능이 있다는 것이 알려짐을 시작으로 1) 최근 임상적 효과로 관절염 3) , 류머티즘 4) , 혈액 Table I이고, 질량 검출기의 조건은 Table II 와 같다. Table I, Table II의 (Fig.…”
Section: 서론»»»unclassified